Prevalensi Dan Faktor Resiko Cestodosis Pada Sapi Bali (Bos Sondaicus) Di Kabupaten Kupang - Jeanet Margareth Daniella Rotte; Aji Winarso; Julianty Almet (Jurnal Veteriner Nusantara, 2022)
Bali cattle are nativeto Indonesia, have distinctive characteristics and high economic value. Bali cattle which only develop on the island of Bali have now spread throughout Indonesia. Bali cattle have advantages, including their resistance to heat and can grow and develop in unfavorable environmental conditions, there fore Bali cattle are widely used in distribution program stotransmigration areas. Kupang Regency as part of the NTT Province is an area that has good potential for cattle production. The laboratory tests consist of a floating test to determine the presence or absence of gastrointestinal cestode eggs and a Mc Master examination to calculate the number of worm eggs per gram offeces. The resultsof the 125 stool samples examined through the floating test contained 25 samples or 20% positive for gastrointestinal cestode eggs. The types of gastrointestinal cestode eggs found in the Balinese calf samples in 5 districts are Moniezia expansa and Moniezia benedeni. From the results of tests conducted by researchers from 125 samples, the average number of livestockowned by breeders was between 11-20 as many as 60 respondents (48%), the livestock rearing system was semi-extensive (released and caged) as many as 61 respondents (48.8%) ), the semi - permanent pen design was 76 respondents (60.8%), the cattle grazing area in the field and at home were 73 respondents (58.4%), the average starting time in the morning was 66 respondents (52.8 %), the type of feed given is mostly grass, as many as 117 respondents with a frequency of 93.6%, a history of being in fected with worms as many as 77 respondents with a percentage of 61.6%, 51 respondents (40.8%) were given independent medicine. , there were 91 respondents (72.8%) for treatment recommendations and 76 respondents (60.8%) who gave worm medicine to cattle when they were sick.